2023
DOI: 10.1007/s00167-022-07299-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent knee extension deficits are common after anterior cruciate ligament reconstruction: a systematic review and meta-analysis of randomised controlled trials

Abstract: PurposeKnee extension deficits complicate recovery from ACL injury and reconstruction; however, the incidence of knee extension loss is not well defined. The aim of this review was to identify the incidence of loss of extension (LOE) following ACL rupture and reconstruction, explore the definitions of knee extension deficits reported and identify prognostic factors affecting LOE incidence. MethodsA systematic search was conducted in Medline, Cochrane Library and PEDro for studies in publication up to November … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Prior to the pilot study two training and familiarization sessions of 2 hours each were performed by the 2 testers. This pilot investigation showed an ICC (2,1) value of approximately 0.85, 0.90, and 0.90 for the universal goniometer, inclinometer, and smartphone app respectively. The subsequent a priori power analysis (testing the null hypothesis H 0 : p=0.8 ICC versus H 1 : p>0.8 ICC) suggested a minimum of 50 participants were required to have an observed power of 80%, (α=0.05) with 2 measurements per participant 21 .…”
Section: Participantsmentioning
confidence: 79%
See 1 more Smart Citation
“…Prior to the pilot study two training and familiarization sessions of 2 hours each were performed by the 2 testers. This pilot investigation showed an ICC (2,1) value of approximately 0.85, 0.90, and 0.90 for the universal goniometer, inclinometer, and smartphone app respectively. The subsequent a priori power analysis (testing the null hypothesis H 0 : p=0.8 ICC versus H 1 : p>0.8 ICC) suggested a minimum of 50 participants were required to have an observed power of 80%, (α=0.05) with 2 measurements per participant 21 .…”
Section: Participantsmentioning
confidence: 79%
“…Knee range of motion (ROM) is a common clinical measurement used to monitor the progress of patients after an anterior cruciate ligament (ACL) injury as 1 out of 3 patients will experience loss of knee extension ROM at 12-month follow-up after this surgery 1 . This deficit could be attributed to multiple of reasons including, but not limited to, inflammation and swelling, surgical problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PF OA is correlated with knee extension deficit [ 5 ]. Knee extension deficit early after ACL reconstruction or at the final follow-up was associated with OA changes [ 13 , 24 ]. However, the present study revealed no significant correlation between preoperative and postoperative extension deficit and new PF cartilage lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical reconstruction is the primary treatment for ACL injury, restoring knee stability [ 7 ]. However, various side effects, including pain and joint contracture, which are triggered by inflammation, are observed after ACL reconstruction surgery [ 11 , 12 , 18 , 29 ]. Steroidal anti-inflammatory drugs (corticosteroids) have been used short-term to alleviate pain and joint contracture after ACL reconstruction, and their effectiveness has been reported [ 18 , 28 ].…”
Section: Introductionmentioning
confidence: 99%